The nature of lesions of the central nervous system in infections, caused by Varicella Zoster virus - S. N. Eshmolov; E. G. Klimovitskaya; M. N. Kuzmina; I. G. Sitnikov (Детские инфекции (Москва))
Varicella Zoster virus can cause damage to the nervous system, more often in the form of meningitis and meningoencephalitis.Purpose: to identify the nature of damage to the central nervous system during infections caused by the Varicella Zoster virus. Materials and methods. The article presents the literature data and the results of own observations of 47 patients treated at the Infectious Diseases Clinical Hospital of Yaroslavl in the period from 2015 to 2021. There were 20 children (42.6%) aged from 18 days to 12 years with chickenpox. There were 27 (57.4%) patients with Herpes Zoster, of which 20 (74.1%) were adults aged 24 to 82 years, 7 (25.9%) were children aged 4 to 14 years. Results. The main clinical and laboratory indicators were analyzed, the features of central nervous system lesions caused by the Varicella Zoster virus were revealed, and the medical and social significance of this problem was confirmed. Among the patients, patients with Herpes Zoster predominated — 27 (57.4%). Meningitis (45.0%), meningoencephalitis (30.0%) and encephalitis (25.0%) were recorded in children with chickenpox. In children with Herpes Zoster, meningoencephalitis predominated (71.4%), while in adults - meningitis (65.0%); there were no encephalitis. There were no deaths, 14.9% of patients were transferred to the neurological department, 85.1% were discharged as outpatients.